Mental Robusthedstræning i Livgarden - Hertz, Eva (Psyke & Logos, 2015)
Over the last two decades, Denmark has sent 26,000 combat soldiers to the Balkans, Iraq and Afghanistan. A large number of veterans have difficulties in adjusting to everyday life after the mission and suffer from sub-clinical symptoms of depression, withdrawal, arousal, and insomnia. The aim of this study was to examine whether resilience training has a positive effect on these symptoms. A pilot study was conducted among a battalion of 130 combat soldiers (ISAF-15) attending a 5-day course on resilience training prior to their deployment to Afghanistan. The curriculum included positive psychology interventions to boost well-being, i.e. training of cognitive skills, self-regulation and identifying character strengths using the VIA-survey. The results were less symptoms of distress, higher scores concerning positive emotions, flexible thinking, and coping strategies. These results persisted 6 months after return from the mission in Afghanistan. This study suggests that resilience training has a significant impact on combat soldiers psychological well-being.